GROWTH AND YIELD OF BUTTERNUT SQUASH AS A RESPONSE TO THE APPLICATION OF ORGANIC FERTILIZER ORIGINATED FROM COW RUMEN LIQUID ON ALLUVIAL SOIL - Sugiarto, Wasi'an, Dini Anggorowati, Agustinus (Jurnal Sains Pertanian Equator, 2019)
Research on the effect of organic fertilizer from cow rumen liquid with various concentrations for growth and yield of butternut squash. The purpose of this study was to find the corrected concentrations of organic fertilizer from cow rumen liquid, which gave the best growth and yield of butternut squash on alluvial soil. The research was carried out in the experimental garden of the Faculty of Agriculture, Tanjungpura University and the duration of the study approximately 3 months (May to July, 2018). The study was designed in a Completely Randomized Design (CRD) with 6 treatments of cow rumen liquid organic fertilizer (P). Each treatment was repeated 4 times, and each replication consisted of 4 plant samples, so the total number of plants were 96. The treatment were a series of the cow rumen liquid organic fertilizer application by with a concentration of p0 = 0% (without cow rumen liquid organic concentrate), p1 = 5% (50 ml of cow rumen liquid organic concentrate in 950 ml of water), p2 = 10% (100 ml of cow rumen organic concentrate in 900 ml of water), p3 = 15% (150 ml of cow rumen liquid organic concentrate in 850 ml of water), p4 = 20% (200 ml of cow rumen liquid organic concentrate in 800 ml of water), p5 = 25% (250 ml of cow rumen liquid organic concentrate in 750 ml of water). The observed variables were the root volume of each plant, total of plant leaf area, total of each plant dry weight, each plant dry root weight, fruit weight of each plant, and fruit diameter of each plants. The results of this study did not obtain the best concentration of organic fertilizer cow rumen liquid, but the administration of organic fertilizer cow rumen liquid at various treatment levels of concentration had an effect on the yield of butternut squash on alluvial soil, namely on the observation variables weight and fruit diameter. Keywords: Butternut squash, Liquid Organic Fertilizer, Alluvial soil